New-onset atrial fibrillation in critically ill acute kidney injury patients on renal replacement therapy - Hellman Tapio; Uusalo Panu; Järvisalo Mikko Johannes (Oxford University Press, 2025)
Aims
The effect of new-onset atrial fibrillation (NOAF) on mortality in critically ill patients with acute kidney injury (AKI) treated in the intensive care unit (ICU) requiring continuous veno-venous haemodialysis (CVVHD) or intermittent haemodialysis (IHD) is unknown. Thus, we examined the incidence of NOAF in critically ill AKI patients undergoing CVVHD or IHD and the association between the timing of NOAF incidence in relation to renal replacement therapy (RRT) initiation and 1-year mortality.
Methods and results
Out of the 733 consecutively recruited ICU patients requiring RRT within the study period of 2010-2019, 516 patients without prior atrial fibrillation history were included in this retrospective study. Clinical comorbidities, medications and biochemistry as well as outcome data for 1-year all-cause mortality were recorded. Episodes of NOAF were collected from the pooled rhythm data covering the entire ICU stay of every patient. The median age was 64 (inter-quartile range 19) years, 165 (32%) were female, and 356 and 160 patients received CVVHD and IHD, respectively. NOAF was observed in 190 (37%) patients during ICU care and 217 (42%) patients died within the 1-year follow-up. Incident NOAF was independently associated with 1-year mortality in the multivariable logistic regression analysis after adjusting for dialysis modality, need for mechanical ventilation or vasopressor support and Acute Physiology And Chronic Health Evaluation II score. However, NOAF diagnosed after RRT initiation was not associated with mortality.
Conclusion
NOAF emerging before RRT initiation is associated with increased mortality in critically ill AKI patients requiring RRT. However, NOAF during RRT does not seem to be associated with mortality.